Physical characteristics of a Dark-Red Latosol (Oxisol) of the Brazilian Savannas ("Cerrados") of Planaltina under fire action - Spera, Silvio Tulio; Reatto, Adriana; Correia, João Roberto; Silva, José Carlos Sousa (Pesquisa Agropecuaria Brasileira, 2000)
The main effects of fire on the soil are related to biological and chemical alterations. Fire can also change the soil moisture as a consequence of alterations in infiltration rates, transpiration rates, porosity, and water repellence. The objective of this work was to evaluate physical characteristics of a heavy clayer Dark Red Latosol (Oxisol) submitted to fire treatments. The selected area of restrict sense Cerrado covers 2.5 ha which have been protected against fire since 1979, despite its use as native pasture during 20 years. The area was divided into two, half of it protected against fire and the other half submitted to fire every two years. Fire has caused no large variations on the physical characteristics of the soil. The non-burnt area has presented an increase on soil moisture. A slight increase of microporosity appeared on the burnt area throughout the period. This could be caused by the rain drops action against the bare soil. Fire every two years was not enough to cause significant degradation on the soil.